Stochastic Assembly of Bacteria in Microwell Arrays Reveals the Importance of Confinement in Community Development - Hansen, Ryan R.; Timm, A. C.; Timm, C. M.; Bible, A. N.; Morrell-Falvey, J. L.; Pelletier, D. A.; Simpson, M. L.; Doktycz, M. J.; Retterer, S. T. (My University, 2016)
The structure and function of microbial communities is deeply influenced by the physical and chemical architecture of the local microenvironment and the abundance of its community members. The complexity of this natural parameter space has made characterization of the key drivers of community development difficult. In order to facilitate these characterizations, we have developed a microwell platform designed to screen microbial growth and interactions across a wide variety of physical and initial conditions. Assembly of microbial communities into microwells was achieved using a novel biofabrication method that exploits well feature sizes for control of innoculum levels. Wells with incrementally smaller size features created populations with increasingly larger variations in inoculum levels. This allowed for reproducible growth measurement in large (20 mu m diameter) wells, and screening for favorable growth conditions in small (5, 10 mu m diameter) wells. We demonstrate the utility of this approach for screening and discovery using 5 mu m wells to assemble P. aeruginosa colonies across a broad distribution of innoculum levels, and identify those conditions that promote the highest probability of survivial and growth under spatial confinement. Multi-member community assembly was also characterized to demonstrate the broad potential of this platform for studying the role of member abundance on microbial competition, mutualism and community succession.
Citation: Hansen, R. H., Timm, A. C., Timm, C. M., Bible, A. N., Morrell-Falvey, J. L., Pelletier, D. A., . . . Retterer, S. T. (2016). Stochastic Assembly of Bacteria in Microwell Arrays Reveals the Importance of Confinement in Community Development. Plos One, 11(5), 18. doi:10.1371/journal.pone.0155080
Keywords: Microbial Communities; Vi Secretion; Lift-Off; Microfluidics; Biofilms; Culture